2019
DOI: 10.3390/f10111038
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Addition Alleviates Microbial Nitrogen Limitations and Promotes Soil Respiration in a Subalpine Coniferous Forest

Abstract: Soil microbes are an important component of soil ecosystems that influence material circulation and are involved in the energy flow of ecosystems. The increase in atmospheric nitrogen (N) deposition affects all types of terrestrial ecosystems, including subalpine forests. In general, alpine and high-latitude ecosystems are N limited. Increased N deposition could therefore affect microbial activity and soil respiration. In this study, four levels of N addition, including CK (no N added), N1 (2 g m−2 a−1), N2 (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…Lower litter N and P, higher lignin content, and the production of phenols would reduce the material circulation speed and finally make the microorganisms subject to carbon and nitrogen limitations (Sinsabaugh et al,2008;Mori et al, 2020). The included angles of the vectors of the alpine shrub island and the tundra control site were higher than 45°, showing that the soil in the alpine region of western Sichuan was limited by phosphorus, which was consistent with the previous research results of our team Zheng et al, 2019).…”
Section: Stoichiometry Of Evergreen and Deciduous Shrub Islandsupporting
confidence: 91%
See 3 more Smart Citations
“…Lower litter N and P, higher lignin content, and the production of phenols would reduce the material circulation speed and finally make the microorganisms subject to carbon and nitrogen limitations (Sinsabaugh et al,2008;Mori et al, 2020). The included angles of the vectors of the alpine shrub island and the tundra control site were higher than 45°, showing that the soil in the alpine region of western Sichuan was limited by phosphorus, which was consistent with the previous research results of our team Zheng et al, 2019).…”
Section: Stoichiometry Of Evergreen and Deciduous Shrub Islandsupporting
confidence: 91%
“…The high temperature difference, low humidity, and high light in the tundra are not conducive to the survival of soil fauna, while the low temperature, high humidity, and low light under the shrub island can serve more soil fauna individuals (Connell 1977;Wu et al, 2014). The difference in soil enzyme activities between the organic layer and the mineral layer under shrub islands showed that the shrub effect significantly affected the decomposition of organic matter in topsoil, while the lack of a difference in control site might be due to the lack of enzyme from the organic layer to the mineral layer due to the difference in soil environment and the fewer number and species of underground biological communities, so that there was no significant difference (Zheng et al, 2019).…”
Section: Effect Of Shrub Islands On the Soil Biological Community And Chemical Characteristicsmentioning
confidence: 96%
See 2 more Smart Citations
“…The fine root samples were oven-dried at 65 ℃ for 48–72 h to a constant weight and then pulverized with a ball mill. The fine root N content was measured using the Kjeldahl method 60 . To analyze the P content, the fine roots were digested with H 2 SO 4 –H 2 O 2 and the molybdenum antimony colorimetric method was applied 61 .…”
Section: Methodsmentioning
confidence: 99%